The Relationship between Parents' Behavior and the Implementation of PHBS Habits in Children During the Covid-19 Pandemic - Ika Rizki Anggraini; Puja Putri Dewi Pati (University of Muhammadiyah Malang, 2021)
Introduction: The condition of the corona virus makes a new change for children starting from learning methods that require a brave system and clean and healthy living habits (PHBS) in everyday life. Objectives: The objective of this research was to find out the correlation between the parents’ behaviors and the clean and healthy life behavioral habits (PHBS) for children during the COVID-19 pandemic. Methods: This research used a cross-sectional method. This research took samples from mothers with children aged 6-12 years old with a total of 45 participants. They were taken randomly. The data collection used questionnaire filling directly. The data analysis used the spearman-rank correlation. Results The findings showed a significant correlation between the parents’ behaviors and the PHBS of the children. The parents’ behaviors toward of the results are excellent behavior (31%) and poor behavior (19%). The spearman test showed a p-value of 0.000. It indicated the correlation of parents with the clean and healthy life habits of children during the COVID-19 pandemic. Conclusions: The parents’ behaviors became the role model for the children to promote the habits of living clean and healthy every day.